The higlander's unexpected bride - Locke, Nicole (Harlequin historicals., 2023)
"Back from battle, Hamilton of Clan Graham makes a bet with his brother to find a wife by summer's end. So, the Scottish warrior enlists the help of his childhood friend, Beileag, to help him woo his perfect woman. But like Hamilton, Beileag has changed whilst he's been away...and she intrigues him like never before! His focus should be on winning a bride. Yet why is Beileag all he can think about?"--